The academic network of pedagogies, peace and resilient populations: its productivity and social relevance - Mora García, José Pascual; Mansilla Sepulveda, Juan Guillermo; Correa Alfonso, José Del Carmen; Fregoso Bailón, Raul Olmo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: to show the intellectual production of the academic network of Pedagogies, Peace and Resilient Populations (PPPR) and its social relevance based on documents of the Educator State. Originality/contribution: Joint work was carried out (groups and institutions) for the analysis of emerging pedagogies, decolonial peace and resilient/vulnerable populations, to improve the quality of life of the sector of the population that has been a victim of political-social conflicts. But also to sensitize the population on a particularly neuralgic issue that concerns the Colombian nation and supranational framework. Method: ethnographic and pluriverse, for this we reflect on the concrete experiences lived at work; and the social impact in the Cundiboyacense context is presented, as well as the actors and the ways of interacting with the community and its projection in the future. Strategies/information collection: The data is filtered from the following sources of study: 1. Combined categories presented to the Scientific Community, among them: Transmodern Peace, Alternative Pedagogies; Resilience Pedagogy; and History of Transmodern Education; 2. Scientific dissemination events; 3. Academic productivity within the research line; 4. The creation of academic programs, e.g. The Doctorate in Education Sciences at the University of Cundinamarca (UdeC); and 5. Research projects completed and in progress. We place ourselves epistemologically in the decolonial and transmodern turn. Conclusions: It is concluded that the PPPR network is committed to the formation, socialization and internationalization with a social rate of return in which the scope of the Final Peace Agreement is internalized. Today, with the results of the Final Truth Report, it is outlined with a prospective vision that vindicates local and translocal environments, as well as the globalized localism.